Os benefícios do uso da gestão do conhecimento em projetos de TI - Moraes, Julio Cesar de Souza (2019)
Knowledge Management (KM) enables different ways of dealing with knowledge and thus can contribute to improve the efficiency of Information Technology (IT) projects. These projects often have many problems such as communication failure, failure to meet deadlines and undefined scope and among others. However, KM is not widespread in organizations yet and should be introduced. One way for this to happen is to highlight its benefits. In this context, the theoretical approach of benefit management (BM) makes it possible to identify the benefits of KM in IT projects. Therefore, the research question to be answered is: What are the benefits of using Knowledge Management in IT projects? To answer this question, after the literature survey on the issue, a set of exploratory interviews were conducted, followed by a focus group. Practitioners, academics and specialists in KM participated in the two qualitative phases of data collection. As the literature still lacks empirical evidence of the value of applying benefit management practices and also on how organizations are embracing BM in IT, the theoretical contribution is to use BM's theoretical approach to identify the benefits of KM in IT projects which are: rationalization of resources; reduction of time, cost and risk; improved employee retention, quality, information and communication management, project innovation, scope maintenance and stakeholder satisfaction. In turn, for practitioners, this research proposes a benefit dependency network to use KM in IT projects.